La regina delle scene e l’imperatore spettatore. Sull’amicizia della Ristori con D. Pedro di Orleans e Bragança - Vannucci, Alessandra (Drammaturgia, 2024)
Adelaide Ristori inaugurated the transatlantic route, triumphing for half a century in theatres around the world and earning the title of ‘queen of the scenes’ endorsed by D. Pedro II, emperor of Brazil. They cultivated an intense friendship, mostly epistolary. They wrote to each other about literature, common acquaintances and travels; however, the actress freely expressed her opinions on current events, while the emperor preferred to comment on performances, acting styles and new repertoires. Observers of an era that saw the end of the Empire in Brazil and the construction of a united Italy, they shared a romantic gaze that did not exclude a heated curiosity about the politics of the present. The public role that Ristori assumed, not giving up being her role as first actress in order to be wife and mother as well as marquise, constituted a model of female emancipation that changed the social perception of the profession. The fact that as ‘queen of the scenes’ she was honoured by kings and emperors gave her a kind of soft power that Cavour valued as a ‘patriotic apostolate’. The diplomatic mission that Ristori took on contributed to the formation of an Italian national identity and was not out of place at the Brazilian court. Showing admiration for the dramatic art, D. Pedro a progressive and cosmopolitan government project, but firmly anchored in European culture. According to him, he was inspired by the ‘enlightened’ government of the Savoys, whom he also approached through Ristori.